UPDRAFT GASIFICATION OF OIL PALM FRONDS - KONDA KUKU, RAMZY ELNEEL (2013)
As a leader in palm oil production, Malaysia produces tremendous quantities of oil palm frond (OPF) during harvesting, pruning and replanting activities period. Up to now, most of the generated fronds are left rotting in the plantations mainly for nutrient recycling resulting in several environmental problems. The huge quantities of fronds every year make them a very promising source for energy generation. Many activates were carried out to convert the fronds into valuable products, but there was no report on study of updraft gasification of oil palm fronds. In this work, small scale updraft gasifier was built to investigate experimentally the behavior and performance of the updraft gasification of oil palm fronds with air as the gasification agent.